ANALISIS FILM MONSTER KARYA HIROKAZU KORE-EDA: DINAMIKA KELUARGA DAN HUBUNGAN INTERPERSONAL - Wildan Fajar Khoerul Anam (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2024)
The film "Monster" (2023) by Hirokazu Kore-eda is a visual exploration of family dynamics and interpersonal relationships. It addresses themes of emotional complexity and the impact of social prejudice on individuals. This research analysis employs qualitative methods through artwork observation and interviews. Additionally, a literature study method is utilized to support the theoretical frameworks in film analysis. The analysis reveals that Kore-eda employs three different perspectives: a single mother, a teacher, and two boys, to illustrate how each character can be seen as a "monster" by others due to misunderstandings and biases. Kore-eda also critiques heteronormative norms and homophobia in Japanese society through recurring narratives and shifts in perspective. This film invites viewers to reflect on the meanings of family, love, and acceptance within the context of complex human relationships, encouraging us to learn how not to become "monsters" to others.